Original paperSingle versus multichannel applicator in high-dose-rate vaginal brachytherapy optimized by inverse treatment planning - Bahadur, Yasir A.; Constantinescu, Camelia; Hassouna, Ashraf H.; Eltaher, Maha M.; Ghassal, Noor M.; Awad, Nesreen A. (Journal of Contemporary Brachytherapy, 2014)
Purpose : To retrospectively compare the potential dosimetric advantages of a multichannel vaginal applicator vs. a single channel one in intracavitary vaginal high-dose-rate (HDR) brachytherapy after hysterectomy, and evaluate the dosimetric advantage of fractional re-planning. Material and methods: We randomly selected 12 patients with endometrial carcinoma, who received adjuvant vaginal cuff HDR brachytherapy using a multichannel applicator. For each brachytherapy fraction, two inverse treatment plans (for central channel and multichannel loadings) were performed and compared. The advantage of fractional re-planning was also investigated. Results : Dose-volume-histogram (DVH) analysis showed limited, but statistically significant difference (p = 0.007) regarding clinical-target-volume dose coverage between single and multichannel approaches. For the organs-at-risk rectum and bladder, the use of multichannel applicator demonstrated a noticeable dose reduction, when compared to single channel, but statistically significant for rectum only (p = 0.0001). For D 2cc of rectum, an average fractional dose of 6.1 ± 0.7 Gy resulted for single channel vs. 5.1 ± 0.6 Gy for multichannel. For D 2cc of bladder, an average fractional dose of 5 ± 0.9 Gy occurred for single channel vs. 4.9 ± 0.8 Gy for multichannel. The dosimetric benefit of fractional re-planning was demonstrated: DVH analysis showed large, but not statistically significant differences between first fraction plan and fractional re-planning, due to large inter-fraction variations for rectum and bladder positioning and filling. Conclusions : Vaginal HDR brachytherapy using a multichannel vaginal applicator and inverse planning provides dosimetric advantages over single channel cylinder, by reducing the dose to organs at risk without compromising the target volume coverage, but at the expense of an increased vaginal mucosa dose. Due to large inter-fraction dose variations, we recommend individual fraction treatment plan optimization.